2021
DOI: 10.1007/s00114-021-01780-8
|View full text |Cite
|
Sign up to set email alerts
|

A parasitoid’s dilemma between food and host resources: the role of volatiles from nectar-providing marigolds and host-infested plants attracting Aphidius platensis

Abstract: The use of nectar-producing companion plants in crops is a well-known strategy of conserving natural enemies in biological control. However, the role of floral volatiles in attracting parasitoids and effects on host location via herbivore-induced plant volatiles is poorly known. Here, we examined the role of floral volatiles from marigold (Tagetes erecta), alone or in combination with volatiles from sweet pepper plant (Capsicum annuum), in recruiting Aphidius platensis, an important parasitoid of the green pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…At four weeks post-inoculation, melon plants infected with CMV, CABYV, or a mixture of both (mixed-infected) were infested with one hundred 2nd-to 3rd-instar nymphs of A. gossypii. All aphids remained on both mock-inoculated and virus-infected plants for a total of 48 h. This ensured that the infesting aphids reached the 4th nymphal instar, providing uniformity in aphid age for subsequent olfactometer bioassays, following a procedure previously described by [36]. Following the infestation period, all melon plants were maintained in a growth chamber at 25:20 • C (Day:Night) temperature, 60-80% relative humidity (RH), and a 16:8 h (Light:Dark) photoperiod during the two days of olfactometer bioassays.…”
Section: Aphid Infestation Of Viral-infected Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…At four weeks post-inoculation, melon plants infected with CMV, CABYV, or a mixture of both (mixed-infected) were infested with one hundred 2nd-to 3rd-instar nymphs of A. gossypii. All aphids remained on both mock-inoculated and virus-infected plants for a total of 48 h. This ensured that the infesting aphids reached the 4th nymphal instar, providing uniformity in aphid age for subsequent olfactometer bioassays, following a procedure previously described by [36]. Following the infestation period, all melon plants were maintained in a growth chamber at 25:20 • C (Day:Night) temperature, 60-80% relative humidity (RH), and a 16:8 h (Light:Dark) photoperiod during the two days of olfactometer bioassays.…”
Section: Aphid Infestation Of Viral-infected Plantsmentioning
confidence: 99%
“…Parasitoids seek an optimal host in a complex process that involves different types of signals (physical, chemical, or visual cues, orientation, alignment, or host quality), being fundamental for female parasitoids in the process of recognizing the host, evaluating and accepting (oviposition) or rejecting their prey in the event that it is not optimal [17]. Thus, behavioral studies have demonstrated the role of plant volatiles in foraging behavior, mainly by female parasitoids, and how they are affected by host phenology, blooming [36], plant biodiversity [43], or plant cultivar [44][45][46]. Recently, Milonas et al [28] found that tomatoes infected by CMV produce plant volatiles that are detected by A. colemani in the absence of its aphid host.…”
Section: Effects Of Volatiles Emitted By Infected Melon On Female Par...mentioning
confidence: 99%
“…9,14,15 Previous studies have screened potential flowering plants for their attractiveness to parasitoids based on their olfactory preferences under laboratory conditions. [16][17][18][19] However, the olfactory preferences of parasitoids may vary depending on their nutritional status, 14,20 experience, 21,22 and learning. 18,23 Parasitoids also respond differently to floral-derived volatile organic compounds (fVOCs) and vegetative parts-derived volatile organic compounds (green leaf volatiles, GLVs), especially those herbivore-induced plant volatiles (HIPVs).…”
Section: Introductionmentioning
confidence: 99%